Police on recruitment drive at convocations - New Sarawak, Tribune (New Sarawak Tribune, 2012)
KUALA LUMPUR: Inspector General of Police Tan Sri Ismail Omar yesterday announced that the Royal Malaysia Police will be holding a recruitment drive for 1,000 Inspectors at upcoming convocations of public and private Institutions of Higher Learning (IHL).